A brief review of grey fuzzy logic technique research progression from 2010 to 2016 - Yacob, Suhaila; Amran Md Ali, Mohd; Ahsan, Qumrul; Arifin, Nurulhuda; Ali, Rafidah (International Journal of Engineering and Technology, 2018)
Grey fuzzy logic method is a new artificial intelligent method that   can make significant improvement in the performance characteristics of the process. In the present study an attempt has been made to provide a brief understanding of the advancement of the Grey Fuzzy Logic from 2010 to 2016. The first half of this paper presents the publication trend of Grey Fuzzy Logic. The remaining of this paper briefly explains the contribution of the individual publication related to Grey Fuzzy Logic. It is believed that this paper will greatly benefit the reader who needs a bird-eyes view of the Grey Fuzzy Logic ’s publications trend.